KAJALI: DALANG WAYANG GARING (Gambaran Perjuangan Dalang Wayang Garing yang Tersisa dari Kikisan Zaman) - Anggita Anggita (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2021)
The production of this film tells the story of a modest life from a leather puppeteer, known as the puppeteer crisp. The fact that the necessities of life is never ending then, Kajali persisted with lack thereof, being the puppeteer as the only of livelihood Kajali. Now, not many traditional arts are able to survive sturdy. Kajali, one of the few people who are still trying to preserve a cultural heritage handed down by their ancestors. This documentary film packaging, adjusted based on the real story intact, so that the audience is expected to see the different side from the figure life of puppeteer in general. As a puppeteer, he utilizes his potential, the potential of humor and good communication to audience as the key to successful of his performance. Hopefully struggle picture of the puppeteer in this documentary can inspire various circles to give attention to revive the nation's cultural assets which tragic fate and danger of being lost without generations inherit.